Pengaruh Optimalisasi Sumber Daya dan Disiplin Belajar terhadap Prestasi Belajar Biologi Siswa dalam Pembelajaran Blended - Tettrinica Meirina (Journal on Education, 2024)
This study explores the influence of optimizing digital resources and learning discipline on student achievement in blended learning. Using a quantitative method with a survey design, data were collected from 150 high school students randomly selected from a population of 500 students. The instrument, a questionnaire, was tested for validity (score > 0.70) and reliability (Cronbach’s Alpha > 0.80), ensuring a reliable measurement tool. Classical assumption tests were conducted, including normality, homogeneity, and multicollinearity tests, which indicated that the data met all prerequisites for multiple linear regression analysis. The analysis results show that optimizing digital resources significantly affects student achievement (Beta = 0.45, p < 0.001), as does learning discipline (Beta = 0.38, p < 0.001). The coefficient of determination (R² = 0.56) indicates that 56% of the variation in student achievement can be explained by these two variables. The limitations of this study include the sample size and specific context. Recommendations for future research are to expand the population scope and explore other factors, such as motivation and social support, for a more comprehensive understanding of the effectiveness of blended learning.